The people's typography : a social semiotic account on the relationship between 'township typography' and South African mainstream cultural production - Venter, Schalk (Dawid Schalk Willem) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.